Prevalence of thyroid dysfunction and anti-thyroid peroxidase antibodies in vitiligo patients - P., Jishna; Binitha, M. P.; Latheef E. N., Abdul; Anilakumari, V. P. (International Journal of Research in Dermatology, 2017)
Background: Vitiligo is associated with various autoimmune diseases, including autoimmune thyroid disease. The objectives of the present study was to determine the prevalence of thyroid dysfunction and anti-thyroid peroxidase antibodies in patients with vitiligo, and to compare the clinical profile of anti-thyroid peroxidase positive and anti-thyroid peroxidase negative patients. Methods: A cross-sectional comparative study was conducted in 100 patients with vitiligo and 100 controls. After dermatologic and systemic evaluation, serum thyroid hormones and anti-thyroid peroxidase antibody levels were measured in all the subjects. Results: Thyroid dysfunction was more common in the vitiligo group (27%) than in the controls. Serum thyroid stimulating hormone abnormalities were more common in the vitiligo group (27%) than in the controls (6%). The most common thyroid dysfunction was subclinical hypothyroidism. Anti-thyroid peroxidase antibody positivity was higher in the vitiligo group (36%) when compared to the controls (24%), and the most common type of vitiligo was vitiligo vulgaris (18%) in this group. Thyroid dysfunction and anti-thyroid peroxidase positivity were more common in women (58%) when compared to men (42%). There was a significantly higher prevalence of other autoimmune diseases in the vitiligo group (20%) compared to the controls (6%). Conclusions: This study shows a significant association between vitiligo and thyroid dysfunction, anti-thyroid peroxidase antibodies and other autoimmune diseases. We recommend that thyroid evaluation and regular follow-up should be done in patients with vitiligo for prompt detection of thyroid dysfunction.